Targeted treatment in patients with non-small cell lung cancer: Use of Bevacizumab and its Biosimilars - Tania, Umme (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.